1999
DOI: 10.1006/viro.1999.9940
|View full text |Cite
|
Sign up to set email alerts
|

Development of Replication-Defective Adenovirus Serotype 5 Containing the Capsid and 3C Protease Coding Regions of Foot-and-Mouth Disease Virus as a Vaccine Candidate

Abstract: A recombinant replication-defective human adenovirus serotype 5 vector containing FMDV capsid, P1-2A, and viral 3C protease coding regions was constructed. Two viral clones were isolated, Ad5-P12X3CWT, containing the wild-type (WT) 3C protease that processes capsid polyprotein precursor into mature capsid proteins, and Ad5-P12X3CMUT, containing a point mutation in the protease coding region that inhibits processing. In 293 cells infected with either virus, synthesis of the FMDV capsid polyprotein precursor occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
61
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(64 citation statements)
references
References 44 publications
0
61
0
1
Order By: Relevance
“…Levels of viremia peak between 2 and 3 days after infection, and there is a rapid development of antibodies correlating with viral clearance. Consistent with this, the presence of neutralizing antibodies correlates with protection against reinfection and is believed to be the important effector function in vaccinated animals (31,33,52). However, the role of innate and cellular immune responses in the protection induced by vaccines is not understood.…”
mentioning
confidence: 85%
“…Levels of viremia peak between 2 and 3 days after infection, and there is a rapid development of antibodies correlating with viral clearance. Consistent with this, the presence of neutralizing antibodies correlates with protection against reinfection and is believed to be the important effector function in vaccinated animals (31,33,52). However, the role of innate and cellular immune responses in the protection induced by vaccines is not understood.…”
mentioning
confidence: 85%
“…Recombinant virus Ad5-pGMCSF was produced by transfection of 293 cells with PacI digested pAd5-pGMCSF following the protocol described (Wu et al, 2003b). The virus was isolated, propagated in 293 cells, and purified by CsCl gradient centrifugation (Mayr et al, 1999;Moraes et al, 2002).…”
Section: Mamentioning
confidence: 99%
“…Plasmid pP12X3C (Mayr et al, 1999), which contains the complete P1-2A and 3C coding regions and partial 2B and 3B coding regions of FMDV A12, was digested with the same enzymes to remove the A12 P1-2A coding region and ligated to O1C P1-2A to generate pP1-2A(O1C)X3C. This plasmid was digested with BglII and XbaI to remove the O1C P1-2A and A12 3C coding regions and ligated to similarly digested Ad5 transfer vector pShuttle (He et al, 1998).…”
Section: Mamentioning
confidence: 99%
See 1 more Smart Citation
“…However, the construct lacked the coding regions for most other nonstructural proteins. 54,55 TEM showed that cells transfected with plasmid pcDNA3.1/P12A3C had detectable empty capsid structures that contained all or most epitopes and induced both humoral and cell-mediated immune responses. We detected isotype-specific sIgA in nasal mucosa samples, and IgA and IgG responses in serum after vaccination of cattle at different time points.…”
mentioning
confidence: 99%